Liquid Marbles: Shape‐Designable Polyhedral Liquid Marbles/Plasticines Stabilized with Polymer Plates (Adv. Mater. Interfaces 24/2020). Issue 24 (17th December 2020) - Fujiwara, Junya; Geyer, Florian; Butt, Hans‐Jürgen; Hirai, Tomoyasu; Nakamura, Yoshinobu; Fujii, Syuji
Abstract : Shape‐designable liquid marbles are prepared using polymer plates as a stabilizer. Thanks to interfacial jamming of the plates, plastic deformation of the liquid marbles is achieved. In article number 2001573, Syuji Fujii and co‐workers are able to fabricate liquid marbles with various shapes including A‐to‐Z letters of alphabet. Liquid marble with the length of > 1.5 m is also prepared.